PERLINDUNGAN HUKUM HAK CIPTA VIDEO DI MEDIA SOSIAL (YOUTUBE) DITAYANGKAN STASIUN TELEVISI TANPA IZIN PENCIPTA BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Lidia Magdalena Mebang (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTVideo is a copyrighted work protected by Law Number 28 of 2014 concerning Copyright. In practice, there are still frequent violations of video copyright works which are the property of a creator, one of the violations that have occurred is when the video is uploaded to the internet site, namely Youtube and the video is shown on television without the permission of the video creator. The problems that arise now are how responsible television stations are to Youtube for videos that are broadcast on television, how legal protection is based on Law Number 28 of 2014 concerning Copyright for creators of videos uploaded on Youtube that are broadcast by television without the author's permission. This research uses normative legal research methods, namely according to the provisions of the law and the provisions of the prevailing laws and regulations. From the results of this research that the Youtube site has provided terms and conditions for video uploaders, and with these rules there will be a legal relationship and will give birth to rights and obligations for video creators and to television stations as third parties who take videos from Youtube that are broadcast on television station by taking the video, the television station must first obtain permission from the creator of the video and include Youtube courtesy (sourced from Youtube) and the name of the video creator. As for the profit earned by television stations by broadcasting the video commercially, the television station must also provide compensation in the form of a request for royalty sharing and the amount of royalty sharing often depends on the mutual agreement of the parties to the video creator.Keywords: Legal Protection, Copyright, Video.